Hadis-Hadis Larangan Bullying dan Implementasinya di Pondok Pesantren Al-Ikhwan Assalam Serapuh - Fera Tamia; Nurliana Damanik; Munandar Munandar (Cetta: Jurnal Ilmu Pendidikan, 2026)
Bullying remains a real problem within Islamic boarding schools (pesantren), even though these institutions are oriented toward the development of Islamic morals and character. The gap between the Islamic values taught and the daily practices of students (santri) serves as the primary background of this research. This study aims to analyze the hadiths of the Prophet Muhammad (peace be upon him) concerning the prohibition of bullying and to examine the implementation of these values in the lives of students at Pondok Pesantren Al-Ikhwan Assalam Serapuh, Langkat Regency, North Sumatra. A qualitative approach with field research was employed, involving 10 informants (1 administrator, 2 caretakers, 1 teacher, and 6 students) selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model and a thematic hadith approach (mawḍū‘ī). The findings reveal that verbal bullying is the most dominant form and is often perceived as joking, thus frequently unrecognized as a violation of Islamic teachings; social bullying was also found, while physical and psychological bullying occurred at lower intensities. Contributing factors include students' limited understanding of bullying boundaries, excessive joking culture, textual religious comprehension, and suboptimal anti-bullying socialization. Implementation of hadith values is carried out through role modeling by caretakers, supervision of student interactions, hadith-based religious instruction, and enforcement of rules with educational sanctions. The study concludes that hadiths prohibiting bullying have strong relevance as a normative foundation for anti-bullying efforts; however, the internalization of these values into students' behavior remains suboptimal. Therefore, strengthening moral development, systematic anti-bullying socialization, and continuous habituation of hadith values are essential to create a safe, harmonious, and Islamically characterized boarding school environment.